SN 2016X: a type II-P supernova with a signature of shock breakout from explosion of a massive red supergiant. Issue 3 (10th January 2018) - Huang, F; Wang, X-F; Hosseinzadeh, G; Brown, P J; Mo, J; Zhang, J-J; Zhang, K-C; Zhang, T-M; Howell, D-A; Arcavi, I; McCully, C; Valenti, S; et al.
Abstract: We present extensive ultraviolet (UV) and optical photometry, as well as dense optical spectroscopy, for type II Plateau (IIP) supernova SN 2016X that exploded in the nearby (∼15 Mpc) spiral galaxy UGC 08041. The observations span the period from 2 to 180 d after the explosion; in particular, the Swift UV data probably captured the signature of shock breakout associated with the explosion of SN 2016X. It shows very strong UV emission during the first week after explosion, with a contribution of ∼20–30 per cent to the bolometric luminosity (versus ≲15 per cent for normal SNe IIP). Moreover, we found that this supernova has an unusually long rise time of about 12.6 ± 0.5 d in the R band (versus ∼7.0 d for typical SNe IIP). The optical light curves and spectral evolution are quite similar to the fast-declining type IIP object SN 2013ej, except that SN 2016X has a relatively brighter tail. Based on the evolution of photospheric temperature as inferred from the Swift data in the early phase, we derive that the progenitor of SN 2016X has a radius of about 930 ± 70 R⊙ . This large-size star is expected to be a red supergiant star with an initial mass of ≳19–20 M⊙ based on the mass–radius relation of the Galactic red supergiants, and it represents one of the most largest and massive progenitors found for SNe IIP.